Pengaruh Pemberian Teh Hitam Terhadap Pertumbuhan Scoby Dan Mutu Fermentasi Kombucha - Artika Rindiani; Gita Syahri Ramadhani; Najwa Liliana; Nita Maya Sari Pane; Zihan Zahriani Batubara; Adelia Febriyossa; Ahmad Shafwan S Pulungan (GLOBAL SCIENTS PUBLISHER, 2025)
Kombucha is a fermented beverage that has been gaining popularity due to its health benefits, such as its antioxidant and probiotic content. One of the main ingredients in making kombucha is tea, and the type of tea used significantly affects the quality of the final product. This study aimed to determine the effect of using black tea on the growth of SCOBY (Symbiotic Culture of Bacteria and Yeast) and the organoleptic quality of kombucha. The research was conducted experimentally at the Microbiology Laboratory of Universitas Negeri Medan in April–May 2025. Kombucha was fermented for six days with a black tea solution to which sugar and a starter culture were added. The parameters observed included SCOBY growth (thickness and diameter) and organoleptic quality (taste, aroma, and color), which were assessed by ten panelists. The results showed an increase in SCOBY thickness from 0.5 cm to 0.8 cm and diameter from 12 cm to 15 cm. Organoleptic tests indicated that black tea kombucha tends to have a sour taste, a moderately strong aroma, and a yellowish-brown to brown color. Based on the research results, it can be concluded that black tea positively influences SCOBY growth and produces kombucha with good sensory quality that is acceptable to the panelists.